2022
DOI: 10.3390/ma15124042
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Assessment of Contemporary Ion-Releasing Restorative Dental Materials

Abstract: The objective was to evaluate new commercially available ion-releasing restorative materials and compare them to established anti-cariogenic materials. Four materials were tested: alkasite Cention (Ivoclar Vivadent) in self-cure or light-cure mode, giomer Beautifil II (Shofu), conventional glass-ionomer Fuji IX (GC), and resin composite Tetric EvoCeram (Ivoclar Vivadent) as a control. Flexural strength, flexural modulus, and Weibull modulus were measured one day, three months, and after three months with accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
2
12
1
Order By: Relevance
“…In addition, an in vitro study [ 31 ] assessed the evolution of mechanical properties of different ion-releasing restorative dental materials over three months and after accelerated aging in ethanol as well as the water sorption and solubility over one year. It was found that the flexural properties of CN were higher than those of a GIC and lower than those of a conventional resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an in vitro study [ 31 ] assessed the evolution of mechanical properties of different ion-releasing restorative dental materials over three months and after accelerated aging in ethanol as well as the water sorption and solubility over one year. It was found that the flexural properties of CN were higher than those of a GIC and lower than those of a conventional resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…The result could be explained by the presence of surface pre-reacted glass-ionomer particles in the giomer; therefore, water sorption does not contribute significantly to fluoride ion release, as shown in a previous study [ 13 ]. In the study by Marović et al [ 25 ] alkasite composite (Cention) showed higher solubility than GIC (Fuji IX Extra) and giomer (Beautifil II), whereas giomer showed the lowest water sorption probably due to the high content of filler particles [ 25 ]. Considering these results and the fact that our specimens were already aged for 25 months prior to being used in the present study, aging can be hypothesized to have altered the material surface and opened porosities where fluoride ions can be deposited and subsequently released.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these results and the fact that our specimens were already aged for 25 months prior to being used in the present study, aging can be hypothesized to have altered the material surface and opened porosities where fluoride ions can be deposited and subsequently released. These considerations may explain why Cention, as the most soluble of all the materials studied [ 25 ], re-released the largest amount of ions.…”
Section: Discussionmentioning
confidence: 99%
“…Initial contact of water with the Cu-MBGN particles exposed on the surface of the composite sample caused a sharp Ca and Cu increase on the first day. However, all composites exhibit different water sorption and solubility degrees depending on their composition and the experimental conditions [ 45 , 46 ]. The water penetrates through irregularities and porosities on the material’s surface and continues its path through the free space to the center of the sample.…”
Section: Discussionmentioning
confidence: 99%